Pyrolysis behavior of sewage sludge produced at Jasin Central sewage treatment plant: article - Yahya, Muhammad Yusri (2019)
Thermochemical conversion of solid fuel is not a new technology today. Pyrolysis is one of the most famous technique that have been widely used in thermochemical conversion process. Pyrolysis of sewage sludge is an economical method where it can manage the volume and the impacts regarding its disposal, thus enabling it into valuable energy and fuel. Sewage sludge can also be defined as semi biomass, but somehow it might complicated than other biomass when it comes to thermochemical conversion. The thermogravimetric analyzer (TGA) is being used to characterize the pyrolysis behaviour of the sewage sludge from Jasin. The proximate and ultimate analysis of the sewage sludge are being compared from the previous researched. Although the pyrolysis of sewage sludge had been studied years ago, but it requires a lot of understanding of its thermal properties.